2017
DOI: 10.1002/adhm.201601198
|View full text |Cite
|
Sign up to set email alerts
|

Biofluid‐Triggered Burst Release from an Adaptive Covalently Assembled Dipeptide Nanocontainer for Emergency Treatment

Abstract: The construction of quickly dissociating containers holding bioactive components that meet the extreme requirements of emergency treatment is highly desirable but remains a great challenge. Here the use of small-molecule-induced dynamic covalent assembly is reported for simple and tunable fabrication of a biocompatible diphenylalanine-based nanocontainer toward rapidly responsive cargo delivery. The assembled nanocontainer can adaptively encapsulate various charged or neutral molecules. Upon biofluid trigger, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…The CDNPs spectrum shows typical amino I at 1600 to 1700 cm –1 , which was attributed to the formation of CN . The CC stretch peaks of the aromatic nucleus at 1386 and 1638 cm –1 became much more intense as a consequence of weakened π–π stacking interactions . The results indicated that there are abundant amino groups on the surface of the CDNPs, which made the CDNPs hydrophilic.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The CDNPs spectrum shows typical amino I at 1600 to 1700 cm –1 , which was attributed to the formation of CN . The CC stretch peaks of the aromatic nucleus at 1386 and 1638 cm –1 became much more intense as a consequence of weakened π–π stacking interactions . The results indicated that there are abundant amino groups on the surface of the CDNPs, which made the CDNPs hydrophilic.…”
Section: Resultsmentioning
confidence: 94%
“…The CDNPs spectrum shows typical amino I at 1600 to 1700 cm −1 , which was attributed to the formation of C N. 27 The CC stretch peaks of the aromatic nucleus at 1386 and 1638 cm −1 became much more intense as a consequence of weakened π−π stacking interactions. 28 The results indicated that there are abundant amino groups on the surface of the CDNPs, which made the CDNPs hydrophilic. Figure 1c,inset shows the X-ray photoelectron spectroscopy (XPS) N 1s spectrum of the sample, which exhibited two fitted peaks at 400.6 and 401.4 that were attributed to the CN and N−H bands, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cationic dipeptide nanoparticles (CDPNPs) can be prepared by mixing a GA aqueous solution with a CDP solution (in HFP) after aging overnight by our reported methods. 28,29 CDPs are the building blocks for the self-assembled CDPNPs with GA as the cross-linking agent. 28 CDPNPs were confirmed to exhibit an adaptive encapsulation property for small molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Self-assembled peptide nanostructures have been demonstrated to be excellent candidates as effective drug carriers. First, with natural amino acid residues as the basic components, peptides have inherent biocompatibility and biodegradability, suitable for various bioapplications. Second, peptides can self-assemble into an array of distinct nanostructures including vesicles, tubes, fibrils, and tapes, which can provide hydrophobic inner cores and hydrophilic outer surfaces for incorporating both hydrophobic and hydrophilic drugs to improve their physiological stability. ,, Moreover, peptides have chemical versatility and can be easily designed to have specific motifs with stimuli-sensitivity and target specificity. , The enzyme-triggered transition of the self-assembled peptide supramolecular nanostructures can be obtained by including an enzyme cleavable sequence in the peptide molecule. , When cancer-specific enzymes are used as stimuli, smart peptide self-assembly systems with a capability of cancer-targeted drug delivery can be developed. ,,,, …”
Section: Introductionmentioning
confidence: 99%